Historic bells in Moravian Missions in South Africa's Western Cape (Historia, 2021)
The Moravian Church was the first denomination to begin with missionary work among the indigenous people in South Africa and today the church still has a very strong presence in the country. After opening their first mission at Genadendal in 1738, a number of further mission stations were established during the nineteenth century in the Western Cape. These missionary stations played an extremely important part in the lives of their residents, both spiritually and socially. In the Moravian Church, as in other churches, their church buildings and the bells accompanying them form an integral part of their heritage. Despite the research that has been carried out on the mission stations per se, no systematic research has been done on the bells at these stations. In this article we discuss these bells, when and where they came from, and who made them. Due to the historical value of these mission stations, we cannot consider the bells without some background discussion of the stations' history. A brief historical background is provided for each station before focusing on the bells at that station and who cast them. Finally, a number of areas for further research are touched upon.  Die Morawiese kerk was die eerste kerkgenootskap wat met sendingwerk onder die inheemse bevolkings van Suid Afrika begin het en vandag het die kerk steeds 'n baie sterk teenwoordigheid in die land. Na die stigting van die eerste sendingstasie te Genadendal in 1738, is 'n aantal verdere sendingstasies gedurende die 19de eeu in die Wes Kaap gevestig. Hierdie sendingstasies het 'n uiters belangrike rol gespeel in die lewens van hul inwoners, op geestelike sowel as sosiale vlak. In die Morawiese Kerk, soos in ander kerke, vorm die kerkgeboue met hul klokke 'n integrale deel van hul erfenis. Ten spyte van vele navorsing wat oor sendingstasies gedoen is, is daar geen sistematiese navorsing oor die klokke op hierdie stasies uitgevoer nie. As gevolg van die historiese waarde van hierdie sendingstasies kan ons nie hul klokke bespreek sonder 'n agtergrond bespreking van die stasies se geskiedenis nie. Dit word vir elke stasie gedoen voordat op die klokke by die stasie gefokus word. Ten slotte word 'n aantal verdere navorsingsareas aangedui.
Keywords: Bell makers; Klokke; Metaalgieters; Kaapkolonie; Mission churches; Cape Colony; Church bells; Erfenis